Effectiveness of different therapeutic measures combined with aerobic exercise as an intervention in patients with depression: a systematic review and network meta-analysis - Chen, Lei; Li, Aichun; Zhou, Junlai; Chen, Wenhao; Kou, Yujia (Frontiers in Psychiatry, 2025)
BackgroundAerobic exercise (AE), as a non-pharmacological therapy, is an effective supplement to conventional depression treatments. However, a comprehensive assessment of combined AE interventions remains insufficient. This study aims to systematically evaluate the intervention effects of different therapies combined with AE in depression patients via network meta-analysis (NMA).MethodsFollowing the PICOS framework, literature was searched in PubMed, Web of Science, Cochrane Library, Embase, Scopus, CNKI, Wanfang, and CBM for randomized controlled trials (RCTs) until June 2024. Independent screening and data extraction were conducted. NMA utilized Stata 15.0 and R 4.4.1, with bias risk assessed by the Cochrane Risk of Bias tool and evidence quality assessed by CINeMA.ResultsA total of 37 RCTs involving 3,362 patients with depression were included, evaluating five combined AE interventions. Results based on the area under the cumulative ranking curve indicated: (1) Hamilton Depression Rating Scale (HAMD): Electroconvulsive therapy + AE (ECT+AE) > repetitive transcranial magnetic stimulation + AE (rTMS+AE) > Traditional Chinese Medicine + AE (TCM+AE) > Selective Serotonin Reuptake Inhibitors + AE (SSRI+AE) > Cognitive Behavioral Therapy + AE (CBT+AE) > Physical Therapy (PT) > Exercise (EX) > CBT > TCM > Control Treatment (CT); (2) Beck Depression Inventory (BDI): SSRI+AE > ECT+AE > CBT+AE > EX > CBT > CT > PT; (3) Self-rating Depression Scale (SDS): TCM+AE > CBT+AE > CT > CBT.ConclusionsCurrent evidence suggests that combined aerobic exercise interventions are superior to monotherapy in the treatment of depression. Of these, SSRI+AE is the most recommended combination, with strong RCT evidence and high-quality evidence ratings. For other AE combination therapies, further validation in large, high-quality trials is necessary in the future.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD42024594873.